(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The use of artificial intelligence, sophisticated robotics technology, big data processing, and their interconnectedness is known as "smart manufacturing," which uses these technologies to improve industrial performance and optimize the energy and manpower needs. Industry 4.0, often known as the fourth industrial revolution, is now all around us, but the idea is not widely accepted. Numerous facets of human existence in all spheres will be enhanced by the adoption of Industry 4.0. The adoption will lead to changes in business paradigms and production models, which will have an impact on supply chains and all stages of production processes, as well as on designers of cyber-physical systems, managers, and end users. For fourth industrial revolution and harness the potential of smart manufacturing process, industrial robots are one of the main component to be employed. Therefore, in this review, the author has provide a quick overview on the type of the robots, the fundamentals about the industrial robots as well as their application and role in different kind activities in manufacturing industries.